THE EFFECT OF CTL-BASED LEARNING VIDEO USE ON THE ABILITY TO COLLABORATE AND COMMUNICATE WITH SCIENCE STUDENTS OF CLASS X SMA NEGERI 1 GIDO - Elman Ikhtiar Ronaldo Waruwu; - Desnita; - Murtiani; Amali Putra (Universitas Negeri Padang, 2021)
This study aimed to see the effect of using CTL-based learning videos on science communication skills and student collaboration in class X MIA SMA Negeri 1 Gido. This study is a quasi-experimental study with a one-group pretest-posttest design. This study uses Class X MIA 2 as the sample class. The data were obtained by using the observation sheet of science communication skills and student collaboration. The results showed that there was an increase in the value of students' science communication skills and collaboration. The posttest score of students' science communication skills was 80.8 and the pretest score was 49.6. The posttest score of students' collaboration ability was 83.8 and the pretest score was 58.2. Based on the results of this study, it can be concluded that there is a positive effect of using CTL-based learning videos on the science communication skills and collaboration of Class X MIA students of SMA Negeri 1 Gido.